Current Management of Trigger Digit in Rheumatoid Arthritis Patients: A Survey of ASSH Members. (November 2022) - Bickham, Rebecca; Carr, Logan; Butterfield, James; Behar, Brittany; Dyer, Ann-Marie; Payatakes, Alexander
Background: Traditional dogma regarding management of rheumatoid arthritis (RA) patients with trigger digit symptoms holds that A1 pulley release should be avoided. Surgical release was thought to further destabilize the metacarpophalangeal joint. Biologic disease modifying anti-rheumatic drugs (DMARDs) have limited the development of hand deformities. Despite advances in RA treatment, many textbooks continue to discourage release of the A1 pulley in RA patients. The aim of this study was to determine if this belief is consistent with current trends in surgical management of trigger digits in patients with RA. Methods: Active Members of the American Society for Surgery of the Hand (ASSH) were surveyed on their training and current practices as related to RA patients with trigger digits. Results: Five hundred three surveys were completed (16% response rate). During training, 55% of ASSH Members were taught to avoid releasing the A1 pulley in RA patients. Seventy-one percent of respondents currently release the A1 pulley in RA patients with no preexisting deformities, no tenosynovial thickening, or if tenosynovectomy and flexor digitorum superficialis slip excision fail to relieve triggering. Forty percent reported that their practice has evolved toward more frequent release of the A1 pulley in RA patients. Conclusion: The majority of ASSH Active Members were taught during training to avoid surgical release of the A1 pulley in RA patients to prevent acceleration of finger deformities. Indications and contraindications for A1 pulley release are evolving along with the improved natural history of RA associated with the use of biologic DMARDs.